1999
DOI: 10.1359/jbmr.1999.14.11.1943
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Analysis of Renal Transplantation Osteoporosis

Abstract: We report a cross-sectional study of 54 adult female renal transplant recipients. We measured bone mineral density (BMD) of the lumbar spine, femoral neck, total hip, and mid-and total radius, and 38 patients underwent transiliac crest bone biopsy. Osteopenia was widespread with 31/54 (57%) of patients osteoporotic at one or more sites. Seventeen out of 54 (32%) of the patients had a prevalent low-trauma fracture. There was a clear trend in BMD reduction across spine, hip and midradius, with the predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
1
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 21 publications
7
41
1
4
Order By: Relevance
“…7 This was a histological classi¢cation, with hyperparathyroidism being classed as the presence of two out of three of the following: increased eroded bone surfaces, elevated osteoclast surface and increased osteoclast numbers. In the adynamic bone disease group, measurements of osteoblast surface, osteoid thickness and osteoclast numbers were all within or below the reference range for age-and gender-matched controls.…”
Section: Methodsmentioning
confidence: 99%
“…7 This was a histological classi¢cation, with hyperparathyroidism being classed as the presence of two out of three of the following: increased eroded bone surfaces, elevated osteoclast surface and increased osteoclast numbers. In the adynamic bone disease group, measurements of osteoblast surface, osteoid thickness and osteoclast numbers were all within or below the reference range for age-and gender-matched controls.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Faugere et al (21) reported a high prevalence of low bone turnover and osteomalacia after RT. Similarly, Parker et al (22) described a pro-gressive reduction in bone turnover which could promote or prolong the adynamic state. However, these were cross-sectional studies performed in mostly symptomatic patients, with various follow-up times.…”
Section: Discussionmentioning
confidence: 95%
“…However, these were cross-sectional studies performed in mostly symptomatic patients, with various follow-up times. Under the conditions described in the study of Parker et al (22), it would not be possible to determine the pre-RT pattern of bone turnover. Therefore, our findings cannot be compared to those from these studies.…”
Section: Discussionmentioning
confidence: 97%
“…Остеопения, остеопоpоз и пеpеломы pазличной ло-кализации -частое осложнение после пересадки почки [9,16,17,18,21]. По данным одномомент-ных исследований, до 40-45% реципиентов как в ранние, так и отдаленные сроки после аллотpанс-плантации тpупной почки (АТП) имеют остеопе-нию, а от 10% до 50% пациентов -остеопороз [7,10,13,14].…”
unclassified
“…Показано, что у женщин-реципиентов значительнее подавлен синтез остеобластами кальцийсвя-зывающего белка остеокальцина [1,2], и риск развития ос-теопороза и переломов костей у них повышен [17]. Однако данные о непосредственной связи между потерями костной ткани и биохимическими маркерами костного обмена [3,14,15], а также между снижением МПК и иммуносупрес-сивной терапией [3,6,8,9,12,14,15,16] в отдаленные сроки после АТП противоречивы. Вместе с тем, по мнению некоторых исследователей, гиперпаратиреоз и связанный с ним повышенный костный обмен -основные предикторы костных потерь в отдаленные сроки после АТП [7,8,14,19].…”
unclassified